2023
DOI: 10.2147/jir.s420721
|View full text |Cite
|
Sign up to set email alerts
|

Differential Characteristics of Patients for Hospitalized Severe COVID-19 Infected by the Omicron Variants and Wild Type of SARS-CoV-2 in China

Abstract: Background: As multiple mutations of SARS-Cov-2 exist, there are now many viral variants with regional differences in distribution. The clinical characteristics of patients hospitalized with the virus also vary significantly, with those of the Omicron variants being strikingly different from those of the earliest wild-type variant. However, comprehensive data on this subject is lacking. It is therefore crucial to explore these differences to develop better clinical strategies for the management of COVID-19. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Our previous multicentre study in Saudi Arabia demonstrated the prognostic value of the NLR in detecting severe COVID-19 cases, i.e., admitted to the ICU, compared to both non-severe cases and non-COVID-19 patients [9]. Such a finding was later confirmed and was found to be applicable to other cohorts locally [15,16] and internationally [17][18][19]. More recently, the works of Regolo et al demonstrated the value of the NLR as an independent predictor of mortality in separate studies including over 1000 patients with COVID-19 [20,21].…”
Section: Discussionmentioning
confidence: 71%
“…Our previous multicentre study in Saudi Arabia demonstrated the prognostic value of the NLR in detecting severe COVID-19 cases, i.e., admitted to the ICU, compared to both non-severe cases and non-COVID-19 patients [9]. Such a finding was later confirmed and was found to be applicable to other cohorts locally [15,16] and internationally [17][18][19]. More recently, the works of Regolo et al demonstrated the value of the NLR as an independent predictor of mortality in separate studies including over 1000 patients with COVID-19 [20,21].…”
Section: Discussionmentioning
confidence: 71%
“…Our previous multicentre study demonstrated the prognostic value of NLR in detecting severe COVID-19 cases, i.e., admitted to the ICU, compared to both non-severe cases and non-COVID-19 patients [11]. Several studies confirmed such findings both locally [20,21] and internationally [12,22]. In more recent studies, Regolo and colleagues demonstrated the value of NLR as an independent predictor of mortality in separate studies including over 1000 patients with COVID-19 [23,24].…”
Section: Discussionmentioning
confidence: 90%
“…With the increased coinfection rate during the Omicron period, routine measurement of procalcitonin was suggested at our institution, and a signi cantly higher procalcitonin level was found in patients during this period. Similarly, the proportion of patients with an increased procalcitonin level on admission was signi cantly higher in patients with the Omicron variant than in those with the wild-type variant (37.2% versus 2.6%) [7].…”
Section: Discussionmentioning
confidence: 91%
“…When the Omicron variant became prevalent [7], patients were more likely to be hospitalized with rather than for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [8,9]. Wei et al [7] found that patients with the Omicron variant were more likely to be older and to have more comorbidities and bacterial coinfections on admission than were patients with the wild-type strain or other variants.…”
Section: Introductionmentioning
confidence: 99%